Farm Gate Energy Intensity of Food Production in Poland - Considering the Physical and Economic Aspects of Production - Łukasiewicz, Joanna; Bajan, Bartłomiej (International Journal of Energy Economics and Policy, 2024)
Within food supply chains, attention is paid to the significant energy consumption at the farm gate level. In agricultural production, the energy intensity of animal production is much higher than that of plant production, but mainly if physical units are considered. This study examines the energy intensity of food production in Poland from 2010 to 2019, contrasting animal and plant production in both physical and monetary units. Utilizing the EXIOBASE database, it compares energy consumption across wheat, sugar beets, pig, and poultry farming sectors, addressing the gap in research on energy intensity within these individual sectors. The research reveals that, contrary to physical unit measurements, the energy intensity in monetary terms is lower for animal production than for plant production. Specifically, plant production showed higher energy intensity, averaging 28.02 MJ/€1 GDP for wheat and 30.15 MJ/€1 GDP for sugar beets. In contrast, animal production had higher energy intensity when measured by physical units, with pigs and poultry averaging 15.72 MJ/kg and 15.36 MJ/kg, respectively. These disparities arise primarily from the greater profitability of animal production, impacting the results per monetary unit. The findings underscore the importance of including economic aspects in energy intensity measurements, influencing agricultural producers’ decisions.